Kegiatan Apresiasi sebagai Sarana Kreativitas Siswa dalam Pembelajaran Seni Tari di SMP Negeri 1 Banuhampu - Indrayuda . (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2012)
This article aims to explain the role of appreciation activities in stimulating students’ creativity in learning the dance art in Junior High School (SMPN) 1 Banuhampu. The appreciation activities are capable of stimulating students to create ideas in performing the moving techniques. In addition, the appreciation activities are able to stimulate students to perform the local dances with a variety of styles. Appreciation activities are displayed by the visual presentation of a variety of local dance performances and a variety of local dance music accompaniment in the audio forms, as well as taking students to the cultural centers such as the Center for West Sumatra Culture (Taman Budaya Sumbar). Keywords: appreciation activities, creativity stimulation, local dance learning